#### Answer

x = -1
y = -4

#### Work Step by Step

3x - y =1
2x - 3y = 10
minus 3x to both sides to the first equation
3x - y - 3x = 1 - 3x
-y = 1 - 3x multiply by ( -1) to both sides
y = -1 + 3x
substitude y to the second equation
2x - 3 ( -1 +3x ) = 10 use the distributive property
2x + 3 - 9x = 10 simplify
- 7x + 3 = 10 minus 3 to both sides
-7x + 3 - 3 = 10 - 3 simplify
- 7x = 7 divide both sides by -7
$\frac{-7x}{-7}$ = $\frac{7}{-7}$
x = -1 substitude x to y = -1 + 3x
y = -1 + $3\times(-1)$
y = -1 -3
y = -4